2008
DOI: 10.1007/s10529-008-9788-0
|View full text |Cite
|
Sign up to set email alerts
|

Locally administered lentivirus-mediated siRNA inhibits wear debris-induced inflammation in murine air pouch model

Abstract: Lentivirus(LV)-mediated small interfering RNA (siRNA) targeting tumor necrosis factor-alpha (TNF-alpha) was locally administered into the air pouch of mice to inhibit inflammation induced by titanium alloy particles. The lentiviral vector expressed green fluorescent protein (GFP) as a reporter gene. Down-regulation of TNF-alpha in pouch area was confirmed by real-time PCR and ELISA, resulting in significantly decreased local inflammatory responses (P < 0.01). This approach was proven safe by localized GFP fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Most of the in vivo studies adopted the murine air-pouch [16,29,33,56,57,58,59,60] and calvarial [18,53,61,62,63,64] models. The first is classically used because it can recreate inflammatory components similar to those of the periprosthetic tissues of osteolytic patients [76]. It is useful for the evaluation of inflammatory and resorption aspects of osteolysis, even if it does not reproduce the physiological situation [77].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the in vivo studies adopted the murine air-pouch [16,29,33,56,57,58,59,60] and calvarial [18,53,61,62,63,64] models. The first is classically used because it can recreate inflammatory components similar to those of the periprosthetic tissues of osteolytic patients [76]. It is useful for the evaluation of inflammatory and resorption aspects of osteolysis, even if it does not reproduce the physiological situation [77].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that adult allo-hUCMSCs just expressed MHC-I, did not express MHCII, therefore, it is promising to be used as allografts to repair tissue defects. More importantly, the proliferation and schizotype of the hUCMSCs permitted the introduction and expression of exogenous gene, so that, it was recommended as a realistic seed cell in adipose tissue engineering [19]- [21].…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus is a non-oncogenic virus; in contrast to other viral vectors, it can infect dividing and non-dividing cells, especially cells that are difficult to transfect, such as primary cells, stem cells and neurons, with an infection efficiency of almost 100%. In addition, lentiviral vectors can effectively integrate, and thus allow consistent expression of, exogenous genes into the chromosome of host cells ( 22 , 23 ), and have attracted increasing attention in the field of gene transfer vectors ( 24 ). Miyoshi et al ( 25 ) demonstrated that GFP is a marker of infection efficiency.…”
Section: Discussionmentioning
confidence: 99%